1
$\begingroup$

I don't really get the absorption law, specifically in this case:

$$ (\lnot p \lor q) \land (\lnot r \lor q) \equiv (\lnot p \land \lnot r) \lor (\lnot p \land q) \lor (q\land \lnot r) \lor (q \land q) $$

The absorption law is used here: $ (\lnot p \land q) \lor (q\land \lnot r) $

I don't really understand the use of absorption law in this case, and if someone could explain it to me on a similar example or something, that would be highly appreciated.

$\endgroup$
  • $\begingroup$ What do you mean, "the absorption law is used here"? Do you mean that it is used to change $ (\lnot p \land \lnot r) \lor (\lnot p \land q) \lor (q\land \lnot r) \lor (q \land q) $ into $ (\lnot p \land q) \lor (q\land \lnot r) $ ? Or do you mean something else? $\endgroup$ – MJD Nov 1 '14 at 15:52
  • $\begingroup$ I mean that it is used here: $ (\lnot p \land q) \lor (q\land \lnot r) $ When we use the absorption law, it cancels out, but I don't get it how? So in the end we only get: $ \lnot p \land \lnot r \lor q $ $\endgroup$ – mythic Nov 1 '14 at 17:54
0
$\begingroup$

With :

$(¬p∧¬r)∨(¬p∧q)∨(q∧¬r)∨(q∧q)$

you first apply $(q \land q) \equiv q$ to simplify it :

$(¬p∧¬r)∨(¬p∧q)∨(q∧¬r)∨q$.

Consider now : $(q∧¬r)∨q$; applying Absorption Laws : $p∨(p∧q) \equiv p$, we have that it is equivalent to $q$.

Thus :

$[(¬p∧¬r)∨(¬p∧q)]∨[(q∧¬r)∨q] \equiv (¬p∧¬r)∨(¬p∧q)∨q$.

Apply it again to : $(¬p∧q)∨q$, which is again equivalent to $q$, to get :

$(¬p∧¬r)∨[(¬p∧q)∨q] \equiv (¬p∧¬r)∨q$.


Regarding absorption :

$p∨(p∧q) \equiv p$

you can prove it with Natural Deduction or verify it via truth table :

  • if $p$ is TRUE, then $p \lor (p \land q)$ is TRUE, by truth table for $\lor$;

  • if $p$ is FALSE, then $(p \land q)$ is FALSE, by truth table for $\land$; so both $p$ and $(p \land q)$ are FALSE, and thus $p∨(p∧q)$ is FALSE, by truth table for $\lor$.

$\endgroup$
  • $\begingroup$ Wow, that clears things up. We were doing this example in college and for some reason we always skip a few steps. I thought we somehow only used the absorption law once, so I really didn't get it. Thank you very much for the explanation, I really appreciate it. $\endgroup$ – mythic Nov 1 '14 at 19:08

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.